TINGKAT AGRESIVITAS AKIBAT PANDEMI COVID-19 PADA MASYARAKAT KOTA JAMBI DITINJAU DARI PENGGUNAAN PROBLEM FOCUSED COPING, EMOTIONAL FOCUSED COPING, RELIGIOUS COPING POSITIVE, DAN RELIGIOUS COPING NEGATIVE: AGGRESSIVENESS LEVEL DUE TO THE COVID-19 PANDEMIC AT JAMBI CITY IN TERMS OF THE USE OF PROBLEM FOCUSED COPING, EMOTIONAL FOCUSED COPING, RELIGIOUS COPING POSITIVE, AND RELIGIOUS COPING NEGATIVE - Lulu Hafina Rozalia; Nofrans Eka Saputra (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2021)
Introduction Covid-19 pandemic was found in Indonesia at 2020, this situation caused various problems starts from economic problem, social to psychological problems. Dealing with various problems that arise due to covid-19, coping or the ability of individuals to responding the problems was necessary so that individuals were able to adapt and keep productive during covid-19 pandemic situation. Objective This study was aimed to prove the existence of differences of aggressiveness level due to the Covid-19 pandemic at Jambi City in terms of the use of problem focused coping, emotional focused coping, positive religious coping, and negative religious coping. Method This research was a quantitative study with a comparative method and cross-sectional. The population in this study were the people of Jambi City with a total sample 401 persons who were determined through purposive sampling technique. The analysis technique used in this research was Anova One Way (F-test) using the JASP 0.14.0.0 application. Result This study show that there were differences of aggressiveness level due to the Covid-19 pandemic at Jambi City in terms of the use of problem focused coping, emotional focused coping, positive religious coping, and negative religious coping with a significant p value of = 0.04 <0.05. These results indicate that the hypothesis in this study was accepted. Conclusions and Recommendation This research concluded that differences of aggressiveness level due to the Covid-19 pandemic at Jambi City in terms of the use of problem focused coping, emotional focused coping, positive religious coping, and negative religious coping. Therefore this research that recommendation to people Jamby city for reduce a aggressiveness with better method for they to do. Keywords: Covid-19 pandemic, agresiveness, coping strategies, religious coping